Review on Adsorption and Photocatalysis of Dyes for Wastewater Treatment - Arfa Ashraf; Syed Muhammad Asif Abbas; Shahzaib Saleem; Shanza Bibi; Rizwan Akbar; Z. Zurat-ul-jannat; Ghulam Hamdani; Nasira Hussain (ASEAN Journal for Science and Engineering in Materials, 2025)
Managing wastewater from dyeing industries has become a significant challenging issue in the world. Various methods have been reported in the literature to treat these effluents with adsorption and photocatalysis emerging as popular methods due to their low cost, simplicity and effectiveness in reducing the quantity of pollutants before they enter water bodies. This review summarizes key findings of the recent few years on the application of metal oxide nanoparticles in wastewater treatment. Adsorption alone is effective for removing pollutants even in very trace amounts, but it does not break down into eco-friendly products. Photocatalysis, on the other side, needs the adsorption of contaminants onto the catalyst surface to initiate degradation. Thus, this review provides a discussion on the mechanism of adsorption, as well as photocatalysis.